Factors Influencing Sustainability Reporting Practices among Listed Companies in Oman - Bhat, Sujatha Ravinarayana; Abdullah, Mohd Asrul Affendi (International Journal of Economics and Financial Issues, 2023)
This paper analyzes the factors influencing sustainability reporting practices among listed companies in Oman during the period 2015–2021. The data was collected from the Muscat Stock Market, covering 133 firm-year observations, and analyzed using multivariate regression analysis. The results show that adoption of sustainability reporting is very low among listed companies, amounting to only 16.5%. Furthermore, 11.6% of the listed companies follow GRI guidelines, and 10.5% of the reports produced take the form of standalone reports. Regarding the factors motivating listed companies in Oman to produce sustainability reporting, the study confirms that company size has a positive impact, while financial leverage and women's presence on boards of directors have a negative impact. The study suggests strengthening institutions and governance, introducing a mandatory reporting system, increasing women's presence on these companies' boards of directors, leveraging new-age technology, promoting capacities among different stakeholders, enhancing awareness of sustainability issues, and incorporating sustainability reporting into corporate strategy so that sustainability reporting is part of the mandates of the listed company to legitimize its existence.